Planning a Medical Lecture - khazaal, Faris Abdul kareem (AL-Kindy College Medical Journal, 2010)
The aims of the lecture should be clearly defmed. These will help to define the teaching methods and the structure. If, for example, the purpose of the lecture is to introduce new knowledge and concepts, then a classic lecture structure might be most appropriate. On the other hand, if the purpose is to make the students aware of different approaches to a particular clinical problem, a problem oriented design in which alternative approaches are presented and discussed might be a more appropriate fonnat. Lectures are still a common teaching methOd in both undergraduate and postgraduak medical education. Properly done, the lectwe is a creative and personal work by the teachll:l modeled upon his intellectual scaffolding. Few other fonns of instructional method demand such a high degree of originality from tire teachers, making it both challenging adtl rewarding for them. Their continued popularity is due to the fact that they represent cr;; effective and efficient means of teaching net’ concepts and knowledge.